Art history the basics - Pooke, Grant; Newall, Diana (Routledge, 2021)
Now in its second edition, this volume is an accessible introduction to the history of art. Using an international range of examples, it provides the reader with a toolkit of concepts, ideas and methods relevant to understanding art history. This new edition is fully updated with colour illustrations, increased coverage of non-western art and extended discussions of contemporary art theory. It introduces key ideas, issues and debates, exploring questions such as: What is art and what is meant by art history? What approaches and methodologies are used to interpret and evaluate art? How have ideas regarding medium, gender, identity and difference informed representation? What perspectives can psychoanalysis, semiotics and social art histories bring to the study of the discipline? How are the processes of postcolonialism, decolonisation and globalisation changing approaches to art history? Complete with helpful subject summaries, a glossary, suggestions for future reading and guidance on relevant image archives, this book is an ideal starting point for anyone studying art history as well as general readers with an interest in the subject.